(untitled) (Bangladesh Journal of Medical Science, 2021)
In December 2019, a novel coronavirus (now named COVID-19) was identified as a causative agent for a cluster of pneumonia cases in Wuhan, China.1 Till March 2020, India was one among 50 countries which identified patients tested positive for COVID-19.2 One day curfew was imposed in the country on March 22, 2020 to forewarn the people about the danger the country was going to face. The government of India announced a nationwide lockdown for 21 days from March 25, 2020 with subsequent second, third and fourth lockdowns. This was done to reduce the transmission of disease and flatten the curve. The preparations to manage COVID-19 pandemic crisis began in Jawaharlal Nehru Medical College Hospital Aligarh, a tertiary care centre in western Uttar Pradesh by 15th of March 2020. In April 2020, it was declared as Level 2 COVID care hospital to deal with complicated and critical cases. The establishment of flu clinic, exclusive COVID-19 isolation ward, teleconsultation and widespread screening of patients by Reverse transcriptase polymerase chain reaction (RT PCR) were some measures undertaken to deal with the crisis. The increased burden of patients presenting with bronchopneumonia necessitated augmentation of the existent infrastructure and better utilization of resources. Emergency and trauma centre, JNMCH, AMU Aligarh was also no exception and reorganising emergency trauma ICU as COVID-19 suspect ICU made the functioning of the entire hospital a lot smoother during this unsustainable crisis situation. However, there were several challenges to overcome while designating an emergency and trauma ICU as COVID-19 suspect ICU. There is ample amount of literature available discussing the strategies for preparing a dedicated COVID ICU, however there is relative scarcity of literature on the challenges in managing an emergency and trauma ICU (ETC – ICU) during the pandemic. In this review, we discuss the strategies and planning for converting an emergency and trauma ICU into a COVID suspect ICU in a tertiary care centre in western Uttar Pradesh (India) during the pandemic and the challenges faced. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.26-31